2018
DOI: 10.1111/acel.12740
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics across 14 Drosophila species reveals signatures of longevity

Abstract: SummaryLifespan varies dramatically among species, but the biological basis is not well understood. Previous studies in model organisms revealed the importance of nutrient sensing, mTOR, NAD/sirtuins, and insulin/IGF1 signaling in lifespan control. By studying life‐history traits and transcriptomes of 14 Drosophila species differing more than sixfold in lifespan, we explored expression divergence and identified genes and processes that correlate with longevity. These longevity signatures suggested that longer‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 93 publications
5
36
1
1
Order By: Relevance
“…[47][48][49][50] As in other animals, aging in D. melanogaster has been shown to affect motor behavior, mating activity, and brain morphology. 60 The study of natural variation in longevity in D. melanogaster has led to the identification of some of the genes involved in longevity; both confirming known pathways (carbohydrate metabolism, cell death, proteolysis), and suggesting new candidate genes for longevity, several of which are without known function. 55 When genes underlying human neurodegeneration due to protein aggregation are expressed in D. melanogaster, age-related protein aggregation occurs by the same mechanism as in human brains.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…[47][48][49][50] As in other animals, aging in D. melanogaster has been shown to affect motor behavior, mating activity, and brain morphology. 60 The study of natural variation in longevity in D. melanogaster has led to the identification of some of the genes involved in longevity; both confirming known pathways (carbohydrate metabolism, cell death, proteolysis), and suggesting new candidate genes for longevity, several of which are without known function. 55 When genes underlying human neurodegeneration due to protein aggregation are expressed in D. melanogaster, age-related protein aggregation occurs by the same mechanism as in human brains.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 92%
“…The study of the transcriptome of 14 different Drosophila species with varied life-span suggested additive small effects of many genes, instead of strong effect of a few. 60 The study of natural variation in longevity in D. melanogaster has led to the identification of some of the genes involved in longevity; both confirming known pathways (carbohydrate metabolism, cell death, proteolysis), and suggesting new candidate genes for longevity, several of which are without known function. 61 Overall, D. melanogaster has been an extremely useful model for elucidating conserved genetic pathways involved in the aging process, 44 as well as identifying epigenetic responses, 62,63 some of which could possibly be plastic and reversible.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 92%
“…For examples, epigenome and transcriptome landscapes with aging in mice have revealed widespread induction of inflammatory responses (Benayoun et al, ); likewise, the downregulation of mitochondrial genes across human tissues has been consistently reported (Glass et al, ; Yang et al, ). Studying transcriptomes across multiple species with varied lifespans has similarly reveled a potential role for gene expression regulation in contributing to longer lifespans (S. Ma et al, ). In addition, epigenetic clock of aging has been developed based on DNA‐methylation markers (Horvath & Raj, ).…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to a social structure where flies interact more equally [43]. Some studies suggest that living in more egalitarian groups correlates with longer lifespans [44] and, interestingly, some of the most sedentary species in our study, such as D. mojavensis and D. virilis , have been reported to have some of the longest life spans across the Drosophila genus [45]. We argue that the differences in group organization seen across drosophilid species is influenced by their different geographic origins and that these differences may correlate with life span.…”
Section: Discussionmentioning
confidence: 75%